Tasarımda Yeni Bir Boyut: Hizmet Tasarımı - İlisulu, İnanç (The Turkish Online Journal of Design Art and Communication, 2015)
The purpose of this research are the description of service design, its appearance and being able to understand this concept in terms of design by examining the coming developments. The pattern of research is “the case study” and the type of research is “illustrative case study” in this work which the qualitative research method was used. “The document review”, that was one of qualitative data collection tools, was used for the purpose of this research. In this study, all the important aspects of service design such as its principles, methodology and tools were explained by examining in depth in the result of document review and analysis. At the end of the study, it is understood that the most important components of service design are consumer experiences and innovation solutions. At the same time, it is seen that the most important components adopt multidisciplinary approach and consumer centred.
Keywords: Hizmet Tasarımı; İnovasyon; Tüketici Deneyimi; Tüketici Merkezli Tasarım; Service Design; İnnovation; Customer Experiences; Consumer Centred Design